Analisis Penerapan E-Bupot Unifikasi Di Instansi Pemerintah Dalam Pemungutan, Penyetoran Dan Pelaporan Spt Masa Februari 2024: (Studi Kasus Dinas Kehutanan Provinsi Jawa Barat) - Dian Anita; Cahya Nilamsari, Amanda (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
E-Bupot Unification is the newest application from the previous version, namely e-Bupot 23/26, which was created to report Periodic SPT. The Directorate General of Taxes provides applications in order to support taxpayers to create proof of withholding and facilitate tax reporting for SPT. Periodic documents are electronic and stored in the Directorate General of Taxes system. This research aims to examine the implementation of Unification E-Bupot, to find out who collects, deposits and reports on the Unification E-Bupot application as well as obstacles to the implementation of Unification e-Bupot in the West Java Provincial Forestry Service. The type of research used in this research is Qualitative Descriptive using primary data. This research applies the interactive model data analysis method proposed by Miles & Huberman, including the process of collecting and reducing data, presenting data, and drawing conclusions. The research results show that the West Java Provincial Forestry Service has implemented the E-Bupot Unification application since 2021, and in making deduction evidence and reporting it is implemented in accordance with the Director General of Taxes Regulation Number PER-24/PJ/2021. With the presence of E-Bupot, every taxpayer can report their Annual Tax Return (SPT) anywhere and anytime online. In implementing the system of proof of collection/withholding and reporting of the unified Periodic Income Tax SPT which has been regulated in the Director General of Taxes Regulation Number PER-24/PJ/2021. The obstacles or obstacles faced when implementing e-Bupot Unification are that the process of opening the DJP website takes quite a long time to load and often experiences errors during the process of inputting and recording period taxes, making it more difficult.